Chiral Metamaterials: A Terahertz Controlled‐NOT Gate Based on Asymmetric Rotation of Polarization in Chiral Metamaterials (Advanced Optical Materials 18/2017). Issue 18 (15th September 2017) - Xu, Wei‐Zong; Shi, Ya‐Ting; Ye, Jiandong; Ren, Fang‐Fang; Shadrivov, Ilya V.; Lu, Hai; Liang, Lanju; Hu, Xiaopeng; Jin, Biaobing; Zhang, Rong; Zheng, Youdou; Tan, Hark Hoe; et al.
Abstract : In article number1700108, a controlled‐NOT (CNOT) gate is demonstrated by Fang‐Fang Ren, Hai Lu, and co‐workers using a double‐layer bi‐anisotropic metamaterial that consists of a planar spiral layer and a cut‐wire layer separated by a polyimide film. Strong asymmetric polarization rotation of two orthogonal linear polarizations is observed when the terahertz waves transmit through the system, which is regarded as the fundamental resource in polarization‐encoded information processing.